Metacognition, metahumanities, and medical education : thinking without the box - Bleakley, Alan (Alan Douglas); Eichbaum, Quentin G.; Ellaway, Rachel (Abingdon, Oxon ; New York, NY : Routledge, 2025)
This persuasive volume develops a novel approach to medical education and the medical humanities, making a case for the integration of the two to explore the ways in which warm' humanism and cold' technologies can come together to design humane posthumanist futures in medicine. There are many problems with conventional medical education. It can be overly technocratic, dehumanizing, and empathy-eroding, introducing artefacts that lead to harm and reproduce inequality and injustice. Use of the arts, humanities, and qualitative social sciences have been pursued as an antidote or balance to these problems. Arguing against the purely instrumentalist use of medical humanities in this way, this book addresses the importance of a genuine and open-ended engagement with humanities approaches in medicine. It discusses the impact of artificial intelligence and emerging theoretical frameworks and posthumanist perspectives, such as object-oriented ontology, on meaning making in medicine. It demonstrates how the key to such a transition is the recovery of the intrinsic art and humanity of metaphor-heavy biomedical science, in turn framed by models of dynamic complexity rather than static linearity. This book is an important contribution to debates around the medical humanities and its role in medical education. It is an essential read for scholars with an interest in these areas, as well as those working in science and technology studies and the sociology of health and illness.
Keywords: Medical education; Medical education -- Philosophy; Medical education -- Social aspects; Metacognition; MEDICAL / Education & Training